Rhetorical yes/no questions in Turkish - Keçeli, Tülin. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2009., 2009)
This study investigates the factors that play a role in interpreting an utterance in the form of a yes/no question as a rhetorical question. The fact that pairs of utterances marked with the same syntactic marker (question particle mI) can be interpreted differently as belonging to an SQ and to an RQ in Turkish has raised the question of whether intonation can mark the function of these utterances. It has been noted in this study that RQs and SQs have different acoustic properties and subjects can identify the type of an utterance through these intonational cues. With respect to the effect of the nature of the TAM markers on the interpretation of utterances as RQs, it has been noted that RQs marked with the aorist and future can be identified more correctly in comparison to utterances marked with the past tense. It has been proposed that in addition to the difficulty in asserting the opposite of a factual event, the prosodic properties of RQs marked with the past tense can also be responsible for the poor performance of subjects in identifying them. With respect to the effect of the nature of the constituent that the question particle mI is cliticized to on the interpretation of utterances as RQs, it has been noted that RQs in which the particle mI follows the subject are identified significantly better than RQs in which the particle mI is cliticized to the verb. To conclude, the fact that utterances in the same form (that of an interrogative) can be identified as RQs or SQs through their intonation supports the claim that intonation functions as a clause-typer in Turkish that marks the function of an utterance belonging to an information-seeking question or belonging to a declarative.
Keywords: Conversation analysis.; Questioning.